From Clicks to Carts: How Social Media Marketing Shapes Brand Awareness and Purchase Intention for Ventela Shoes in Indonesia - Vira Aulia Rahmi; Lailan Tawila Berampu; Taufiqurrahman (CV. Rayyan Dwi Bharata, 2026)
The rapid growth of social media has transformed how companies interact with consumers, particularly in the fashion industry where trends are strongly influenced by digital exposure. Although Social Media Marketing (SMM) enhances brand visibility, its effectiveness in directly driving purchase intention remains uncertain, especially for local brands such as Ventela. This study aims to analyze the effect of SMM on Purchase Intention with Brand Awareness as a mediating variable. A quantitative approach was employed using a survey method involving 157 respondents aged 17–26 years selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that SMM has a significant effect on Brand Awareness but does not directly influence Purchase Intention. In contrast, Brand Awareness significantly affects Purchase Intention and mediates the relationship between SMM and Purchase Intention. These results indicate that social media marketing is more effective in influencing purchase intention when it first strengthens brand awareness. The study implies that companies should prioritize engaging digital content and interaction strategies to enhance brand awareness as a key pathway to influencing consumer purchasing decisions.